Freaky tales [videorecording (DVD)] - Boden, Anna; Fleck, Ryan, 1976-; Pascal, Pedro; Hanks, Tom; Ellis, Jay, 1981-; Mendelsohn, Ben (Lionsgate, 2025)
An NBA star, a corrupt cop, a female rap duo, teenage punks, neo-Nazis and a debt collector embark on a collision course in 1987 Oakland, California.